Implementation of electronic word of mouth and service quality toward repurchase intention at K Club Ubud Resort - Ni Wayan Okta Piani; I Gusti Agung Mas Krisna Komala Sari; I Gusti Agung Bagus Mataram (Journal of Applied Sciences in Travel and Hospitality, 2024)
This study aims to know the implementation and the influence of electronic word of mouth (E-WOM) and service quality towards repurchase intention at K Club Ubud Resort and determine which factors are the most dominant in increasing repurchase intention. The data collection used was observations, documentation, questionnaires, interviews, and literature studies with a total sample of 31 which was determined by the non-probability sampling method, namely saturated sampling. The data analysis technique is a mixing method design that refers to the explanatory sequential design, where quantitative analysis uses multiple linear regression analysis in the first stage and then is analyzed in more depth with qualitative descriptive analysis. The results of this study conclude that K Club Ubud Resort has implemented electronic word of mouth and service quality, where the determination coefficient found is 77,6%. The dominant factor based on the effective contribution value shows that service quality has the highest score (49,5%), followed by electronic word of mouth (28,1%). This phenomenon is caused by the stipulation of service standards which are the source of consumer satisfaction at K Club Ubud Resort. With excellent service, consumers will feel satisfied and will come to visit again (repurchase intention). Besides that, consumers will also promote the products they bought previously at K Club Ubud Resort either by word of mouth or through social networking sites.